Etika Agama di Tengah Krisis Moral Bangsa - Alois A. Nugroho (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2016)
Our nation moral crisis is closely related to our incapability to do what so-called “expanding the circle” in the moral deliberation today. The corruptors and black merchants in some way are the people who want to “feed” their family, and it means also the “extended family”. So, we are too naive if judge them as a group of egoistic people. Yet, we can say that they suffer a moral “myopia”. Their solitude horizon is very narrow. They only think the goodness of their near surrounsings. Their horizon does not reach the “nation area” or “national interest”, let alone “human being” and “the future of people,” “ecological care.”